2015
DOI: 10.1039/c4cc08522a
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy to construct a FRET platform for ratiometric sensing of hydrogen sulfide

Abstract: We introduce a new FRET strategy to construct a ratiometric fluorescent H2S sensor. The ratio emission signal of the coumarin-naphthalimide dyad is modulated by the FRET process, which works in coordination with the ICT mechanism. The FRET process on/off is controlled through tuning the overlap level of the donor emission spectrum with the acceptor absorption via modulation of the acceptor fluorophore absorption wavelength. was applied to visualize both the intracellular exogenous and endogenous H2S through bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…Over the past several years, fluorescent chemosensors have been developed as useful sensors for various metal ions due to their simplicity, specificity and sensitivity monitoring with a fast response time [27][28][29]. Therefore, various fluorophores with different excitation and emission wavelengths, such as coumarin [30,31], pyrene [32,33], 1, 8-naphthalimide [34,35], xanthenes [36,37], squaraine [38], cyanine [39], boron dipyrromethene difluoride (BODIPY) [40], and nitrobenzofurazan [41], have been employed to develop various chemical sensors. Among the developed fluorophores, rhodamine and its derivatives [42,43] employ an ideal framework in the construction of fluorescent probes due to their excellent spectroscopic properties including high fluorescence quantum yield, large molar extinction coefficient, and visible wavelength excitation [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, fluorescent chemosensors have been developed as useful sensors for various metal ions due to their simplicity, specificity and sensitivity monitoring with a fast response time [27][28][29]. Therefore, various fluorophores with different excitation and emission wavelengths, such as coumarin [30,31], pyrene [32,33], 1, 8-naphthalimide [34,35], xanthenes [36,37], squaraine [38], cyanine [39], boron dipyrromethene difluoride (BODIPY) [40], and nitrobenzofurazan [41], have been employed to develop various chemical sensors. Among the developed fluorophores, rhodamine and its derivatives [42,43] employ an ideal framework in the construction of fluorescent probes due to their excellent spectroscopic properties including high fluorescence quantum yield, large molar extinction coefficient, and visible wavelength excitation [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…It is not easy to build these FRET‐based ratiometric fluorescent platforms because they require considerable spectral overlap between the emission of the donor and the absorption of the acceptor. However, intramolecular charge transfer (ICT) could trigger the absorption redshift and quantum yield increase of the fluorophore . It could be used to change the level of spectral overlap of the FRET‐based fluorescent platforms to switch the FRET process on/off.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin and naphthalimide are widely used as fluorophores owing to their high photophysical properties . Furthermore, there is good spectral overlap between the emission of coumarin and the absorption of naphthalimide . To obtain more efficient probes, we changed the overlap level by adjusting the naphthalimide absorption wavelength to exert on/off control over the FRET process.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the large number of chromogenic receptors for the sensing of metal ions, [11][12][13] very few chromogenic receptors for anions and small molecules have been developed that are based on recognition approaches. [13][14][15][16] In fact, a thorough literature survey revealed that there are very few colorimetric or fluorogenic sensors which dealt with the use of synthetically constructed receptors in carboxylic acids sensing purpose. [17][18] Supramolecular concepts [19][20] in designing new optical chemosensors has become a very common trend in recent-past based on changes in fluorescence [21][22][23] and in absorbance [24][25][26] as the output signals.…”
mentioning
confidence: 99%